2013
DOI: 10.3109/0886022x.2013.817316
|View full text |Cite
|
Sign up to set email alerts
|

Severe recurrent rhabdomyolysis-induced acute kidney injury in a HIV-infected patient on antiretroviral therapy

Abstract: Antiretroviral medications, specifically tenofovir, have been linked to acute tubular necrosis in humans with a suggested mechanism of direct tubular injury. Rhabdomyolysis has rarely been described in patients on highly active antiretroviral therapy (HAART). To the best of our knowledge, severe recurrent rhabdomyolysis-induced acute kidney injury (AKI) in a HIV-infected patient on two different triple antiretroviral regimens has not been reported. We present a HIV-positive patient who first developed heme pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…21 Delaying administration of HAART in HIV patients with AKI prevents further renal injury from the medications' nephrotoxic nature. 22 Prior to discontinuation upon hospitalization, our patient's HAART regimen consisted of lopinavir and ritonavir. The patient endorsed compliance with his HAART regimen prior to hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Delaying administration of HAART in HIV patients with AKI prevents further renal injury from the medications' nephrotoxic nature. 22 Prior to discontinuation upon hospitalization, our patient's HAART regimen consisted of lopinavir and ritonavir. The patient endorsed compliance with his HAART regimen prior to hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Although the lopinavir/ritonavir combination drug has been investigated as a potential treatment regimen for COVID-19, there has been conflicting evidence in terms of efficacy. [21][22][23][24][25][26] Some studies have reported a reduction of symptoms and SARS-CoV-2 viral load when initiated early in the treatment course. 2 Despite the recommendation by early studies that lopinavir/ritonavir should be used in vulnerable populations with COVID-19 pneumonia, more evidence is needed to enforce this practice.…”
Section: Discussionmentioning
confidence: 99%
“…The patient described here presented with acute kidney injury AKIN stage III induced by severe rhabdomyolysis that was diagnosed 10 days after the introduction of Genvoya®. The main causes of rhabdomyolysis comprise crush injury, burns, infections, medications, drug use, and extreme exercise [2]. Acute kidney failure is a frequent complication [3, 4].…”
Section: Discussionmentioning
confidence: 99%
“…Ritonavir can cause nephrotoxicity itself [7] as well as increase levels of other medications used concomitantly. Spiegel et al [32] described a case of acute renal failure in a patient receiving abacavir. Serum creatinine levels reflect renal function, and the positive correlation between β 2 M and serum creatinine shown in our study confirms its usefulness.…”
Section: Discussionmentioning
confidence: 99%